Functional and Degenerative Mitral Regurgitation: One Ring Fits All? - Sideris, Konstantinos; Boehm, Johannes; Voss, Bernhard; Guenther, Thomas; Lange, Ruediger S.; Guenzinger, Ralf (The Thoracic and Cardiovascular Surgeon, 2019)
Background Three-dimensional saddle-shaped annuloplasty rings have been shown to create a larger surface of leaflet coaptation in mitral valve repair (MVR) for functional mitral regurgitation (FMR) and degenerative mitral regurgitation (DMR) which may increase repair durability. For the first time, this study reports mid-term results after MVR for DMR and FMR using a rigid three-dimensional ring (Profile 3D, Medtronic).Methods Between June 2009 and June 2012, 369 patients with DMR (n = 326) or FMR (n = 43) underwent MVR (mean age 62.3 ± 12.6 years). A total of 205 patients (55.6%) underwent isolated MVR and 164 patients (44.4%) a combined procedure. Follow-up examinations were performed in 94.9% (mean 4.9 ± 0.9 years). Echocardiographic assessment was complete in 93.2% (mean 4.3 ± 1.2 years).Results The 30-day mortality was 1.5% (5/326) for DMR (1.5% for isolated and 1.6% for combined procedures) and 9.3% (4/43) for FMR (0% for isolated and 10.5% for combined procedures). Survival at 6 years was 92.1 ± 1.9% for DMR (92.9 ± 2.6% for isolated and 90.7 ± 2.7% for combined procedures) and 66.4 ± 7.9% for FMR (80.0 ± 17.9% for isolated and 63.7 ± 8.9% for combined procedures). Cumulative risk for mitral valve-related reoperation at 6 years was 0% for FMR and 7.1 ± 1.5% for DMR. At echocardiographic follow-up, one patient presented with mitral regurgitation (MR) more than moderate. The only predictor of recurrent MR after MVR for DMR was residual mild MR at discharge.Conclusion Repair of FMR with the three-dimensional Profile 3D annuloplasty ring shows excellent mid-term results with regard to recurrence of MR. In cases of DMR, the results are conforming to the current literature.
Keywords: mitral valve; heart valve; surgery; outcome